2021
DOI: 10.1007/s11665-020-05366-9
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Characterization of Thin-Walled Tube Manufactured with Selective Laser Melting for Stent Application

Abstract: This paper focuses on microstructural and mechanical characterization of metallic thin-walled tube produced with additive manufacturing (AM), as a promising alternative technique for the manufacturing of tubes as a feedstock for stents micromachining. Tubes, with a wall thickness of 500 μm, were made of 316L stainless steel using selective laser melting. Its surface roughness, constituting phases, underlying microstructures and chemical composition were analyzed. The dependence of hardness and elastic modulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Even the corrosion process did not alter the roughness significantly, rather the forming degradation layer adapted to the 3D structure of the underlying substrate. For conventional stents in the field of cardiovascular application, a roughness Ra < 0.5 μm is envisaged . In ongoing studies, we address this issue of surface treatment to decrease macro roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Even the corrosion process did not alter the roughness significantly, rather the forming degradation layer adapted to the 3D structure of the underlying substrate. For conventional stents in the field of cardiovascular application, a roughness Ra < 0.5 μm is envisaged . In ongoing studies, we address this issue of surface treatment to decrease macro roughness.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to ref 14, owing to the addition of the electret; the viscosity of the suspension used for electrospinning decreases, and consequently, the brittleness of fibers increases with agglomeration of electret content. We adopted the maximum value of (5% PU–9% PANI–0.5% SiO 2 ) stress–strain to calculate a Young’s modulus of 0.11 MPa and based on the equation where σ and ε are the stress and the corresponding strain, respectively. We also tested the shape recovery property and tensile elasticity; the results indicated that the sub-micron fiber patch was not broken during hand stretching and could keep integrity for several seconds under 250 g counterpoise load (Figure b–e).…”
Section: Resultsmentioning
confidence: 99%
“…The root mean squared roughness (R q ) and arithmetic average roughness (R a ) of the microblasted stent strut surfaces were reduced from 3.17 AE 0.58 and 2.66 AE 0.58 μm for glass treatment and 2.88 AE 1.08 and 2.34 AE 0.86 μm for corundum treatment compared with the as-built surface 3.94 AE 0.77 and 3.27 AE 0.62 μm, respectively. [45] Conventional laser cut stents for cardiovascular applications need an arithmetic average roughness <0.5 μm, [51] Table 2. Roughness of as-built stent struts and after microblasting with glass beads and corundum particles.…”
Section: Surface Characterizationmentioning
confidence: 99%